ANALISIS ARUS KAS UNTUK PENGAMBILAN KEPUTUSAN PADA CV ELSA MANDIRI ABADI - Danik Karyawati; Sumawan; Ahmad Khudori; Megananda Haris Arlyn (JAMER : Jurnal Akuntansi Merdeka, 2024)
The cash flow report is a very important part of a company which describes the amount of cash receipts and expenditures. The cash flow report consists of operating activities, investment activities, and financing activities. To maintain the continuity of the company, a cash flow is very necessary and the company can read the cash flow calculations for decision making. The research aims to find out whether information on cash flow from operating activities is a step in making company management decisions. The research was carried out at CV Elsa Mandiri Abadi, located on Jalan Setia Budi, Klegen Madiun. The type of research is descriptive qualitative. The results of the research are the adequacy of the company's operating cash flow to meet all its needs is quite good. The results of the overall ratio calculation are an analysis of the ratio of operating cash flow to current debt, the ratio of operating cash flow to total debt, the interest coverage ratio the ratio of cash flow to net profit, and the quality ratio. sales for 3 periods in the company that cash flow can be used as a management decision-making tool because the results are positive. Management decision-making includes: 1) Consider purchasing fixed assets; 2) Fixed assets that are not useful should be sold to be realized as cash; and 3) Companies need to reduce expenditure items and make efficiencies to increase profit margins